Woven Fabric Triboelectric Nanogenerator for Biomotion Energy Harvesting and as Self-Powered Gait-Recognizing Socks - Chaoyu Chen (Energies, 2020)
In recent years, rapid advancements have developed in multifunctional and wearable electronics, which call for more lightweight, flexible energy sources. However, traditional disposable batteries and rechargeable batteries are not very suitable because of their bulky appearance, limited capacity, low flexibility, and environmental pollution problem. Here, by applying a mature manufacturing technology that has existed in the textile field for a long time, a woven fabric triboelectric nanogenerator (WF-TENG) with a thinner structure that can be mass-fabricated with low cost, perfect stability, and high flexibility is designed and reported. Due to the good intrinsic quality of TENGs, the maximum voltage of this WF-TENG can easily reach 250 V under a pressure of 3.5 kPa and a tapping frequency of 0.33 Hz. Because of the stable plain-woven structure, the output voltage can remain relatively stable even after the WF-TENG has been working for about 5 h continuously, clearly demonstrating its robustness and practical value. Moreover, good sensitivity endows this WF-TENG with the capability of being applied as self-powered sensors, such as a self-powered smart real-time gait-recognizing sock. This WF-TENG shows us a simple and effective method to fabricate a wearable textile product with functional ability, which is very meaningful for future research.